Why do knowledge workers choose knowledge hiding: the mediating role of perceived stress - Bai, Yina; Xiao, Yuxin (Frontiers in Psychology, 2026)
IntroductionIn today's knowledge-driven economy, knowledge workers are central to sustaining innovation, yet the phenomenon of Knowledge hiding—the deliberate withholding of requested knowledge—poses a serious challenge to collaboration and organizational performance. Drawing on conservation of resources theory, social exchange theory, and stress interaction theory, this study explores how Workplace Ostracism and task complexity influence knowledge hiding, emphasizing the mediating role of Perceived stress and the moderating role of Perceived pay fairness.MethodsData were collected from 330 knowledge workers in Beijing through a two-wave survey combining online and offline questionnaires. Workplace Ostracism, task complexity, perceived stress, knowledge hiding, and perceived pay fairness were measured using validated scales. Hierarchical regression, confirmatory factor analysis, and bootstrapping techniques were applied to test direct, mediating, and moderating effects.ResultsThe results indicate that both Workplace Ostracism and Task complexity significantly and positively predict Knowledge hiding, with Perceived stress partially mediating these effects. Furthermore, Perceived pay fairness negatively moderates the relationship between Perceived stress and Knowledge hiding, as well as the indirect effects of Workplace Ostracism and Task complexity via Perceived stress. Specifically, high levels of Perceived pay fairness weaken these positive associations, whereas low levels exacerbate them.DiscussionThis study makes three key contributions. First, it enriches the literature on Knowledge hiding by introducing a stress-perception perspective and highlighting Perceived stress as a central explanatory mechanism. Second, it extends conservation of resources theory and social exchange theory by identifying Perceived pay fairness as a critical boundary condition. Third, it offers actionable guidance for organizations, suggesting that enhancing compensation fairness, fostering inclusion, and managing task demands can mitigate stress-induced Knowledge hiding and promote effective knowledge sharing.